Association of different doses of antenatal corticosteroids exposure with early major outcomes and early weight loss percentage in extremely preterm infants or extremely low birthweight infants: a multicentre cohort study - Ying Zhou; Qi Feng; Haijun Wang; Xiaofang Huang; Xiuying Tian; Yong Ji; Shuaijun Li; Shufen Zhai; Rongxiu Zheng (BMJ Publishing Group, 2024)
Objectives To determine the dose-dependent associations between antenatal corticosteroids (ANS) exposure and the rates of major morbidities, and the early weight loss percentage (EWLP) in hospital among extremely preterm infants (EPI) or extremely low birthweight infants (ELBWI).Methods A multicentre, retrospective cohort study of EPI or ELBWI born between 2017 and 2018 was conducted. Infants were classified into no ANS, partial ANS and complete ANS exposure group; three subgroups were generated by gestational age and birth weight. Multiple logistic regression and multiple linear regression were performed.Results There were 725 infants included from 32 centres. Among no ANS, partial ANS and complete ANS exposure, there were significant differences in the proportions of bronchopulmonary dysplasia (BPD) (24.5%, 25.4% and 16.1%), necrotising enterocolitis (NEC) (6.7%, 2.0% and 2.0%) and death (29.6%, 18.5% and 13.5%), and insignificant differences in the proportions of intraventricular haemorrhage (IVH) (12.5%, 13.2% and 12.2%), and extrauterine growth restriction (EUGR) (50.0%, 56.6% and 59.5%). In the logistic regression, compared with no ANS exposure, complete ANS reduced the risk of BPD (OR 0.58, 95% CI 0.37 to 0.91), NEC (OR 0.21, 95% CI 0.08 to 0.57) and death (OR 0.36, 95% CI 0.23 to 0.56), and partial ANS reduced the risk of NEC (OR 0.23, 95% CI 0.07 to 0.72) and death (OR 0.54, 95% CI 0.34 to 0.87). Compared with partial ANS exposure, complete ANS decreased the risk of BPD (OR 0.58, 95% CI 0.37 to 0.91). There were insignificant associations between ANS exposure and IVH, EUGR. In the multiple linear regression, partial and complete ANS exposure increased EWLP only in the ≥28 weeks (w) and <1000 g subgroup (p<0.05).Conclusions Different doses of ANS (dexamethasone) exposure were protectively associated with BPD, NEC, death in hospital, but not EUGR at discharge among EPI or ELBWI. Beneficial dose-dependent associations between ANS (dexamethasone) exposure and BPD existed. ANS exposure increased EWLP only in the ≥28 w and<1000 g subgroup. ANS administration, especially complete ANS, is encouraged before preterm birth.Trial registration number NCT06082414.